The D. melanogaster capa-1 neuropeptide activates renal NF-kB signaling. - Terhzaz, S.; Overend, G.; Sebastian, S.; Dow, J.A.; Davies, S.A. (Peptides, 2014)
The capa peptide family exists in a very wide range of insects including species of medical, veterinary and agricultural importance. Capa peptides act via a cognate G-protein coupled receptor (capaR) and have a diuretic action on the Malpighian tubules of Dipteran and Lepidopteran species. Capa signaling is critical for fluid homeostasis and has been associated with desiccation tolerance in the fly, Drosophila melanogaster. The mode of capa signaling is highly complex, affecting calcium, nitric oxide and cyclic GMP pathways. Such complex physiological regulation by cell signaling pathways may occur ultimately for optimal organismal stress tolerance to multiple stressors. Here we show that D. melanogaster capa-1 (Drome-capa-1) acts via the Nuclear Factor kappa B (NF-kB) stress signaling network. Human PCR gene arrays of capaR-transfected Human Embryonic Kidney (HEK) 293 cells showed that Drome-capa-1 increases expression of NF-kB, NF-kB regulated genes including IL8, TNF and PTGS2, and NF-kB pathway-associated transcription factors i.e. EGR1, FOS, cJUN. Furthermore, desiccated HEK293 cells show increased EGR1, EGR3 and PTGS2 - but not IL8, expression. CapaR-transfected NF-kB reporter cells showed that Drome-capa-1 increased NF-kB promoter activity via increased calcium. In Malpighian tubules, both Drome-capa-1 stimulation and desiccation result in increased gene expression of the D. melanogaster NF-kB orthologue, Relish; as well as EGR-like stripe and klumpfuss. Drome-capa-1 also induces Relish translocation in tubule principal cells. Targeted knockdown of Relish in only tubule principal cells reduces desiccation stress tolerance of adult flies. Together, these data suggest that Drome-capa-1 acts in desiccation stress tolerance, by activating NF-kB signaling.